MEMBERIKAN PELATIHAN DI LOKA BINA KARYA UNTUK MENGEMBANGKAN KREATIFITAS HASIL PRODUK BUATAN SENDIRI - Nufzatutsaniah Nufzatutsaniah; Kris Dipayanti; Bunga Astra Gracia; Rian Sri Rahayu; Raden Yeti Sumiaty (LPPM Universitas Pamulang, 2020)
On 2,3,4 December 2019, we had successfully carried out Community Service activities at the Bina Karya Workshop located at Jalan Jagakarsa 1 No.10 Rt.005 / 02 Jagakarsa, South Jakarta. The Purpose of Community Service Activities is to carry out the Tri Dharma of Higher Education. Also expected from the results of this activity is that universities can contribute to the development and application of science to the community, especially in the target people in Loka Bina Karya. The method used in this activity is training of fostered citizens to develop creativity from the results of homemade products. The result of community service obtained is the increase in knowledge of the target people. The knowledge gained by fostered citizens in community service activities is expected to be able to provide motivation and provision of knowledge for fostered citizens in the future.Keywords: training, development, creativity